JUSTIÇA RESTAURATIVA: COVID-19 E SAÚDE MENTAL (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
This article presents the experience of the Center for Legal Practice at Centro Universitário Santa Amélia, in Ponta Grossa-PR, in the application of virtual peacebuilding circles in the context of social isolation caused by the COVID-19 pandemic. The circle is a method of Restorative Justice, which I define here as a simple but profound program for building more meaningful relationships and increasing emotional awareness. The negative psychological impacts of the coronavirus quarantine motivated the migration from face-to-face to online circles, understanding that circular practice can contribute to building a support network and strengthening bonds between people. With this objective, 96 circles were carried out in three semesters, involving 738 people, and the result was the perception that the circle, even virtually, is able to promote self-knowledge and interpersonal connection in a deep and meaningful way, contributing positively with mental health in the pandemic.